Identifying with Antarctica in the Ecocultural Imaginary - Nielsen, H (Routledge, 2020)
Antarctica is physically inaccessible for most, but it lives in the imaginations of many. In this chapter, I argue imagined versions of place play an important role in why and how even distant locations such as Antarctica are valued. Given the impact of highly extractive and polluting ecocultural identities and histories, Antarctica cannot be seen as a place apart from the rest of the world. Rather, the continent needs to be understood as a place of global importance, and one that can be incorporated into the ecocultural identities of those all over planet Earth. I examine the case studies of two Antarctic documentaries that focus on humans who live and work on the continent: Werner Herzogs Encounters at the End of the World (2007) and Antony Powells Antarctica: A Year on Ice (2014). The chapter asks how such documentaries can bring Antarctica into everyday consciousness of people around the world, challenge preconceptions about the far south, and help audiences reimagine their own human connections and interactions with the ice.